Helicobacter pylori first-line and rescue treatments in patients allergic to penicillin: Experience from the European Registry on H pylori management (Hp-EuReg) - Nyssen, Olga P; Pérez-Aisa, Ángeles; Tepes, Bojan; Rodrigo-Sáez, Luis; Romero, Pilar M; Lucendo, Alfredo; Castro-Fernández, Manuel; Phull, Perminder; Barrio, Jesús; Bujanda, Luis; Ortuño, Juan; Areia, Miguel; et al. (Helicobacter, 2020)
BACKGROUND: Experience in Helicobacter pylori eradication treatment of patients allergic to penicillin is very scarce. A triple combination with a PPI, clarithromycin (C), and metronidazole (M) is often prescribed as the first option, although more recently the use of a quadruple therapy with PPI, bismuth (B), tetracycline (T), and M has been recommended. AIM: To evaluate the efficacy and safety of first-line and rescue treatments in patients allergic to penicillin in the "European Registry of H pylori management" (Hp-EuReg). METHODS: A systematic prospective registry of the clinical practice of European gastroenterologists (27 countries, 300 investigators) on the management of H pylori infection. An e-CRF was created on AEG-REDCap. Patients with penicillin allergy were analyzed until June 2019. RESULTS: One-thousand eighty-four patients allergic to penicillin were analyzed. The most frequently prescribed first-line treatments were as follows: PPI + C + M (n = 285) and PPI + B + T + M (classic or Pylera® ; n = 250). In first line, the efficacy of PPI + C + M was 69%, while PPI + B + T + M reached 91% (P < .001). In second line, after the failure of PPI + C + M, two rescue options showed similar efficacy: PPI + B + T + M (78%) and PPI + C + levofloxacin (L) (71%) (P > .05). In third line, after the failure of PPI + C + M and PPI + C + L, PPI + B + T + M was successful in 75% of cases. CONCLUSION: In patients allergic to penicillin, a triple combination with PPI + C + M should not be generally recommended as a first-line treatment, while a quadruple regimen with PPI + B + T + M seems to be a better option. As a rescue treatment, this quadruple regimen (if not previously prescribed) or a triple regimen with PPI + C + L could be used but achieved suboptimal (<80%) results.
Keywords: Anti-Bacterial Agents; bismut; prospektivní studie; Tetracycline; tetracyklin; Humans; lidé; Drug Hypersensitivity; registrace; Penicillins; klarithromycin; Levofloxacin; Prospective Studies; Bismuth; Helicobacter Infections; peniciliny; infekce vyvolané Helicobacter pylori; antibakteriální látky; léková alergie; Metronidazole; Proton Pump Inhibitors; inhibitory protonové pumpy; kombinovaná farmakoterapie; Drug Therapy, Combination; Registries; Clarithromycin; levofloxacin; Helicobacter pylori; metronidazol